Statin use, HMGCR expression, and breast cancer survival – The Malmö Diet and Cancer Study - Bjarnadottir, Olöf (Sci Rep, 2020)
Statins, commonly used to treat hypercholesterolemia, have also been proposed as anti-cancer agents. The identification of a predictive marker is essential. The 3-hydroxy-3-methylglutaryl-coenzyme-A reductase (HMGCR), which is inhibited by statins, might serve as such a marker. Thorough antibody validation was performed for four different HMGCR antibodies. Tumor expression of HMGCR (#AMAb90619, CL0260, Atlas Antibodies, Stockholm, Sweden) was evaluated in the Malmö Diet and Cancer Study breast cancer cohort. Statin use and cause of death data were retrieved from the Swedish Prescribed Drug Register and Swedish Death Registry, respectively. Breast cancer-specific mortality (BCM) according to statin use and HMGCR expression were analyzed using Cox regression models. Three-hundred-twelve of 910 breast cancer patients were prescribed statins; 74 patients before and 238 after their breast cancer diagnosis. HMGCR expression was assessable for 656 patients; 119 showed negative, 354 weak, and 184 moderate/strong expressions. HMGCR moderate/strong expression was associated with prognostically adverse tumor characteristics as higher histological grade, high Ki67, and ER negativity. HMGCR expression was not associated with BCM. Neither was statin use associated with BCM in our study. Among breast cancer patients on statins, no or weak HMGCR expression predicted favorable clinical outcome. These suggested associations need further testing in larger cohorts.